U.S.-Finland Economic Relations 1917- 1945 - Ali Ghafil Hasan (Genius Journals, 2021)
Following Finland's declaration of independence from the Russian Empire in 1917, the US established diplomatic relations with the country in 1919. Finland's economy was helped by a financial loan from the United States of America. As a young, fledgling nation, the United States expended a significant deal of effort in forging strong commercial relations with Finland. In 1933, President Franklin D. Roosevelt advocated the zero-interest proposal as a way to repay Finland's debt. Because of the Treaty of Amity and Commerce of January 13, 1934, Finland considers the United States to be an important commercial partner. During World War II, the United States broke diplomatic relations with Finland in 1944. The US government has declared a desire to investigate the potential of re-establishing diplomatic relations with Finland since October 1944. In 1945, diplomatic relations between Finland and the United States were restored. Finland is bordered on the east by Russia, and as a Soviet Union neighbor, it was of special interest and importance to the US both during and after the Cold War.
Keywords: U.S; Finland; Economic; Relations